2016
DOI: 10.1111/irj.12143
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of equality legislation: the case of disabled graduates and reasonable adjustments

Abstract: This article explores how reasonable adjustments, part of UK equality legislation, are secured in the workplace, and argues that an implementation gap exists where the impact of the law is weak, despite legal mandates to aid disabled people in employment. The research points to the importance of employers' knowledge of the effects disability as a key determinant of securing workplace adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…They identified factors that inhibited the ability of line managers to comply with formal policies, many of which included HRM practices (e.g., training). The second study was based on qualitative data of new graduate disabled employees in the United Kingdom; William (, p. 349) found that when disabled employees worked for an organization that had a specialist equality and diversity HR manager, they were better able to secure reasonable adjustments than when they were absent, “even when formal policies existed.” In fact, this research found that in organizations where there was a formal policy related to the provision of reasonable adjustment for disabled employees without corresponding HRM practices, adjustments were either difficult to achieve or failed altogether.…”
Section: Introductionmentioning
confidence: 99%
“…They identified factors that inhibited the ability of line managers to comply with formal policies, many of which included HRM practices (e.g., training). The second study was based on qualitative data of new graduate disabled employees in the United Kingdom; William (, p. 349) found that when disabled employees worked for an organization that had a specialist equality and diversity HR manager, they were better able to secure reasonable adjustments than when they were absent, “even when formal policies existed.” In fact, this research found that in organizations where there was a formal policy related to the provision of reasonable adjustment for disabled employees without corresponding HRM practices, adjustments were either difficult to achieve or failed altogether.…”
Section: Introductionmentioning
confidence: 99%
“…A further type is where discrimination is alleged because the employer has failed to provide a reasonable adjustment for the disabled employee, for example, shorter working hours or adjustments to physical premises. 3 Such a legal provision, which may involve treating the disabled person more favourably than their non-disabled colleagues, is rarely understood by employers, but unless adjustments are made, disabled people experience disadvantage, and failure to make reasonable adjustments can be claimed (William, 2016). If any part of a claimant's claim is successful, compensation can be awarded for material loss and injury to feelings, but in practice, compensation is modest: the median in the year from April 2017 was £16,523 (Ministry of Justice, 2019), and because Employment Tribunals have no power to enforce their money judgments, claimants may not even receive their award.…”
Section: Taking a Casementioning
confidence: 99%
“…A further type is where discrimination is alleged because the employer has failed to provide a reasonable adjustment for the disabled employee, for example, shorter working hours or adjustments to physical premises. Such a legal provision, which may involve treating the disabled person more favourably than their non‐disabled colleagues, is rarely understood by employers, but unless adjustments are made, disabled people experience disadvantage, and failure to make reasonable adjustments can be claimed (William, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are also indications that the Reasonable Adjustments Duty has encouraged adjustments (e.g., [38], p. 56). However, adjustments appear to be quite often not made when there could well have been a legal duty to make them or when there might not have been a duty but making them would have benefited the individual and the organisation (e.g., [39,40]). For example, Chaplin and Davidson ([41], p. 1) state "The results showed that people who develop a dementia while still in employment do not always receive the 'reasonable adjustments' in the workplace to which they are entitled under the Equality Act (2010)".…”
Section: The Impact Of Disability Discrimination Lawmentioning
confidence: 99%